(untitled) (Acta Scientiarum. Animal Sciences, 2025)
Seed propagation is the most used method for producing yellow passion fruit seedlings (Passiflora edulis f. flavicarpa); however, the success and uniformity of seedling formation are influenced by the germination process. This study aims to evaluate the influence of light and different pollination conditions on the quality of passion fruit seeds and seedlings. The experiment was conducted in two stages, both arranged in a completely randomized design (CRD): In the first stage, two treatments were used to determine the optimal light conditions for the germination of Passiflora edulis seeds obtained from fruits formed through manual cross-pollination (MCP). In the second stage, the effects of different pollination conditions on seed germination and seedling development were evaluated. The variables analyzed included germination rate, mean germination time, germination speed index, total seedling length, shoot length, root length, and fresh and dry biomass. The results indicated that the absence of light promotes a higher germination rate and a shorter mean germination time for P. edulis seeds. Flowers subjected to manual cross-pollination (MCP) and free visitation without pollen thieves (FVWT) resulted in higher germination rates and shorter germination times. The presence of thieves caused a 31% reduction in seed germination but did not affect seedling development.